PUBLIC LIBRARIES IN THE WESTERN PROVINCE OF SRI LANKA: A RESEARCH STUDY - Nalini, M.A. (MASTERS' DEGREE OF LIBRARY SCIENCE, 1995)
Public libraries in the Western Province were subjected to a study by means of data collected through a questionnaire answered by the librarians concerned. The analysis of data revealed that public libraries are faced with several problems in fulfilling the obligations of these institutions in terms of the UNESCO public library manifesto. Basically the inadequacy of funds allocated for library services and lack of sufficient physical facilities together with lack of sufficient reading materials in the minority languages came to light in this investigation. The provision of sufficient user accommodation and more building facilities where buildings are inadequate, establishment of branch libraries in suburban areas, more reading materials for minority communities, longer opening hours for suburban libraries and finally more financial allocations for the development of public libraries are the major areas to be considered by the authorities. The introduction and development of electronic media for library services is a further recommendation to be focused by the authorities.